Efficacy of Beeswax and Essential Oil Coatings on Preserving Quality and Extending Shelf Life of Unripe Mangoes (Mangifera indica) - Busola Tumininu Ayangbemi; Kunle Ogungbemi; Boluwaji M Adenyi; Ayokunle O Alejo; Samuel T Popoola; Oluwakemi M Solomon-Ibuwunwa (UMYU Journal of Microbiology Research)
This study evaluated the performance of Mangifera indica fruits coated with beewax admixed with some essential oils which includes cinnamon, lavender and clove oil. Weight loss, colour change and some chemical analysis were used to adjudge the quality preservation and shelf life extension of the Mangifera indica fruits. The weight of Mangifera indica fruits coated with all the treatments decreased over the period of observation; however, fruits coated with beewax admixed with lavender oil had the least weight loss (2.94%). The colour varied from green to yellow with black spot, where beewax coated and beewax admixed with lavender oil retained pale green throughout the study. Also, there was a significant increase in pH and a decrease in titratable acidity (TTA) of samples in the control plot. The study therefore concludes that edible coatings tested demonstrated great potential in maintaining the overall quality compared with untreated control. Beeswax mixed with lavender coating effectively delayed ripening of the Mangifera indica fruits for an additional 6 days as indicated by the reduction of weight loss, total titratable acidity and pH.